The Shigella Type III Secretion Effector IpaH4.5 Targets NLRP3 to Activate Inflammasome Signaling - Wang, Xiaolin; Sun, Jin; Wan, Luming; Yang, Xiaopan; Lin, Haotian; Zhang, Yanhong; He, Xiang; Zhong, Hui; Guan, Kai; Min, Min; Sun, Zhenxue; Yang, Xiaoli; et al. (Frontiers in Cellular and Infection Microbiology, 2020)
Activation of the NLRP3 inflammasome requires the expression of NLRP3, which is strictly regulated by its capacity to directly recognize microbial-derived substances. Even though the involvement of caspase-1 activation in macrophages via NLRP3 and NLRC4 has been discovered, the accurate mechanisms by which Shigella infection triggers NLRP3 activation remain inadequately understood. Here, we demonstrate that IpaH4.5, a Shigella T3SS effector, triggers inflammasome activation by regulating NLRP3 expression through the E3 ubiquitin ligase activity of IpaH4.5. First, we found that IpaH4.5 interacted with NLRP3. As a result, IpaH4.5 modulated NLRP3 protein stability and inflammasome activation. Bacteria lacking IpaH4.5 had dramatically reduced ability to induce pyroptosis. Our results identify a previously unrecognized target of IpaH4.5 in the regulation of inflammasome signaling and clarify the molecular basis for the cytosolic response to the T3SS effector.